Instrumentos para análise da ocorrência de trauma na infância: revisão da literatura - Bragiola, Thaís [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Studies show that childhood trauma not only predisposes the individual to psychopathologies in adulthood, but also are associated with the maintenance of long-term emotional disorders. OBJECTIVE: The purpose of this study was to verify which are the main instruments available in the scientific literature to evaluate the history of childhood trauma in adults and to carry out a brief review of the most frequently used questionnaires. METHODS: A review of the narrative literature was carried out, where inclusion criteria were studies that: 1) were published in the English language; 2) were carried out between 2008 and 2018; 3) had abstracts available for the research; 4) made the retrospective evaluation of childhood trauma in adults; 5) collected data on traumatic events through an interview or questionnaire. We excluded from the study articles that did not provide enough information about the evaluation instruments or that did not use an interview or questionnaire to assess childhood trauma. RESULTS AND DISCUSSION: Initially 4269 articles were found in the research using the keywords. The studies were evaluated and 442 articles met the inclusion criteria. Were evaluated 29 instruments that analyze the occurrence and frequency of childhood trauma and the most used in the studies were used the Childhood Trauma Questionnaire (CTQ) in 77.60%, followed by the Childhood Experience of Care and Abuse (ECSC-Q) used in 5.65 % of the studies, Adverse Childhood Experiences Questionnaire (ACE-Q) in 3.16% of the articles and finally the Early Trauma Inventory (ETI) used...

Estudos mostram que o trauma na infância não só predispõe o indivíduo a psicopatologias na fase adulta, como também estão associados à manutenção de desordens emocionais a longo prazo. OBJETIVO: O presente estudo teve o objetivo de verificar quais são os principais instrumentos disponíveis na literatura cientifica para avaliação do histórico do trauma infantil em adultos e realizar uma breve revisão dos questionários mais utilizados. MÉTODOS: Foi realizado uma revisão de literatura narrativa, onde os critérios de inclusão foram estudos que: 1) foram publicados no idioma inglês; 2) foram realizados no período entre 2008 e 2018); 3) tinham resumos disponíveis para a pesquisa; 4) fizeram a avaliação retrospectiva do trauma na infância em adultos; 5) coletaram os dados sobre os eventos traumáticos por meio de entrevista ou questionário. Foram excluídos do estudo os artigos que não ofereciam informações suficientes sobre os instrumentos de avaliação ou que não utilizaram entrevista ou questionário para avaliação do trauma na infância. RESULTADOS E DISCUSSÃO: Inicialmente foram encontrados um total de 4269 artigos na pesquisa com o uso das palavras-chaves. Os estudos foram avaliados e 442 artigos satisfizeram os critérios de inclusão. Foram avaliados 29 instrumentos que analisam a ocorrência e frequência do trauma infantil e os mais utilizados nos estudos foram o Childhood Trauma Questionnaire (CTQ) em 77,60% dos artigos, seguido do Childhood Experience of Care and Abuse (CECA-Q) usado em 5,65% dos estudos. Adverse Childhood Experiences Questionnaire (ACE-Q) em 3,16% dos artigos e por fim o Early Trauma Inventory (ETI) utilizado em 2,03%. CONCLUSÃO: esta revisão atualizada da literatura indicou que a avaliação retrospectiva em adultos de experiências traumáticas vividas na infância apresenta...
Keywords: Trauma psicológico; Maus-tratos infantis; Psychological trauma